Hubungan Fear Of Missing Out (Fomo) Terhadap Tingkat Kecemasan Mahasiswa Fikes Universitas YPIB Majalengka - Sri Wahyuni; Muhammad Rafli Febriansyah; Suyanti Suyanti (MEJORA Medical Journal Awatara, 2026)
Background. Social media has become an inevitable aspect of student life, particularly for the younger generation. Fear of Missing Out (FoMO) and anxiety have emerged as significant issues, especially among health faculty students who actively engage with social media. Objective. This study aims to examine the relationship between Fear of Missing Out (FoMO) and anxiety levels among students of the Faculty of Health Sciences (FIKes) at YPIB Majalengka University in 2025. Methods. This study employed a quantitative design with a cross-sectional approach. A sample of 89 students was selected using stratified random sampling. Data were collected using the Fear of Missing Out Scale (FoMOs) and the Social Anxiety Scale for Social Media Users (SAS-SMU). Data analysis was performed using the Chi-Square test with a significance level of 0.05. Results. The findings revealed that a small proportion (6.7%) of students experienced high FoMO, while more than half (71.9%) reported high anxiety levels. However, no significant relationship was found between FoMO and anxiety levels (p value= 0.115). Conclusion: Although a statistically significant relationship was not found, the descriptive results indicate a high prevalence of anxiety among students. Interventions such as digital literacy education, anxiety management training, and enhanced social support are recommended to improve students' mental well-being.